Ca2+-Calmodulin regulation of testicular androgen production in Mozambique tilapia (Oreochromis mossambicus) - Martins, Rute S. T. (2014)
The Ca2+-Calmodulin (CaM) signaling pathway has previously been shown to be involved in the regulation of teleost fish ovarian steroidogenesis. However, a putative role of CaM in testicular steroidogenesis and potential targets has not been examined. To examine whether basal steroidogenesis is modulated by Ca2+ and CaM levels in the testis of Mozambique tilapia (Oreochromis mossambicus) we have incubated testicular fragments in vitro under different conditions and analyzed steroid output. Calcium-free medium with or without EGTA did not affect testicular basal 11-ketotestosterone (11-KT) and testosterone (T) secretion. However, addition of 80 lM the CaM inhibitor W7 significantly reduced basal 11-KT, T and androstenedione secretion. Interestingly, the decreased androgen production by 80 lM of W7 was accompanied by increased 11-desoxicortisol output and by the activation of cortisol synthesis in the testis, the latter undetected in untreated tissues. However, production of 17,20a-dihydroxy-4-pregnen- 3-one was unaltered by W7. This suggests that C17,20 desmolase, 21-hydroxylase and possibly 11bhydroxysteroid dehydrogenase are targets for CaM. In addition, androgen production was also found to be regulated by the level of cAMP since incubations with forskolin (FK) significantly increased 11-KT and T output. A cross-talk between the cAMP and Ca2+-CaM signaling pathways was detected since W7 administration also decreased FK stimulated androgen production. Altogether, these data show that both basal and cAMP stimulated androgen levels were modulated by intracellular Ca2+-dependent CaM and that possibly Ca2+-CaM determines the shift in steroidogenesis from C21 steroids to androgens.